Flood Disaster Evacuation Analysis (Case Study: Long Pahangai I Village and Long Pahangai II Village, Mahakam Ulu Regency) - Novita Mebang; Ardiyanto Maksimilianus Gai; Annisa Hamidah Imaddudina (Universitas KH. Abdul Chalim Mojokerto, 2025)
Flood disasters are caused by high rainfall intensity and the close proximity of residential areas to the river, as observed in Long Pahangai I and Long Pahangai II Villages. Flooding in these villages occurs frequently every year, with varying water levels. In 2024, floods occurred more than twice in May, reaching a water level of 3 meters above the road surface. Currently, there are no designated evacuation points for flood disasters in the study area. However, during flooding events, affected residents typically seek refuge in unaffected homes within the community. Given this situation, it is crucial to consider the characteristics of the area when planning for flood disaster evacuation. The evacuation point planning process takes into account the capacity and characteristics of the study location, while evacuation routes are determined using Network Analysis to identify the most effective paths. The analysis results indicate the identification of two temporary evacuation points, one final evacuation point, and three flood disaster evacuation routes distributed across Long Pahangai I and Long Pahangai II Villages.